2017
DOI: 10.1177/1078345817699595
|View full text |Cite
|
Sign up to set email alerts
|

Inmate Health Care Provided in an Emergency Department

Abstract: The United States has the highest rate of incarceration in the world. Many correctional facilities have outsourced the medical care for this population that often presents with complex health issues. This study evaluates the reasons that inmates present to an emergency department (ED) and compares them to the general population ED visits. The most common presenting complaints were trauma (16.8%), abdominal pain (13.5%), chest pain (9.0%), and self-injury (8.7%). These presenting complaints differed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
3
1
0
Order By: Relevance
“…The high prevalence of head and facial trauma in this population likely arises from the increased risk of interpersonal violence among incarcerated persons. These data are in agreement with single-center reports from SUNY-Upstate and Bellevue Hospital in New York City, which showed facial trauma (mandible and other facial fractures) is the most common injury pattern for justice-involved individuals at their facilities 16,17 . Our study also found almost one third of patients had a closed head injury.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high prevalence of head and facial trauma in this population likely arises from the increased risk of interpersonal violence among incarcerated persons. These data are in agreement with single-center reports from SUNY-Upstate and Bellevue Hospital in New York City, which showed facial trauma (mandible and other facial fractures) is the most common injury pattern for justice-involved individuals at their facilities 16,17 . Our study also found almost one third of patients had a closed head injury.…”
Section: Discussionsupporting
confidence: 92%
“…These data are in agreement with single-center reports from SUNY-Upstate and Bellevue Hospital in New York City, which showed facial trauma (mandible and other facial fractures) is the most common injury pattern for justice-involved individuals at their facilities. 16,17 Our study also found almost one third of patients had a closed head injury. A meta-analysis of 33 studies on traumatic brain injury in prison facilities worldwide calculated a mean prevalence of 46%, with approximately 37% resulting from interpersonal violence.…”
Section: Epidemiologysupporting
confidence: 66%
“…However, considering that many mental disorders are associated with a certain level of aggressiveness 29 and therefore a higher risk of lesions (traumas/limb problems), the findings may be assessed under the same prism. On the other hand, our findings match the ones in the American study, where trauma was the main reason for visiting A&E (16.8%) 30 .…”
Section: Discussionsupporting
confidence: 90%
“…This does not include psychiatric disease since state prisons often triage psychiatric illness to internal psychiatric units. However, emergency department (ED) admission data from Tennessee and New York State show that 4% and 13% of presenting diagnoses were psychiatrically related [37,38] This is likely, however, due to differences in baseline co-morbidities between immigrant and local populations: Among non-immigrant patients who presented to ED from prisons, 35% have a comorbidity of hypertension, 16% have a comorbidity of coronary artery disease, 11% have a comorbidity of diabetes, and 45% have a comorbidity of psychiatric illness [38].…”
Section: Discussionmentioning
confidence: 99%